Hyperpigmentation: A Rare Presentation of Celiac Disease - . Shyama; N. Kumar (Current Practice in Medical Science Vol. 8, 2022)
Celiac disease, an immune mediated enteropathy has wide spectrum of manifestations. Manifestations may be intestinal or extraintestinal. Hyperpigmentation is a known symptom of Vitamin B12 deficiency, but Vitamin B12 deficiency with only hyperpigmentation is uncommon. We present a case of coeliac disease with nutritional anaemia (vitamin B12, S. folate, iron) and hyperpigmentation caused by vitamin B12 deficiency. Our patient was not having any intestinal complaints at the time of presentation. She came from Eastern part of India where rice is one of the stable diet and her preference to rice over wheat might have been the reason for masking of intestinal symptoms. Hyperpigmentation was reversible and improved on B12 supplementation.